Cinematic Sequence For Video Blog Using Multimedia Development Life Cycle - Tony Wibowo; Lisanto Lisanto (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2021)
There are so much video blog on internet. It already become a trend for now, where people can record and upload video to internet and can be watched by audiences. But because some video blog has boring visual, especially lack of cinematic content in the video blog. And with cinematic videos is actually can attract more audience. Therefore with this video blog can help people understand how to make cinematic sequence with some tips on this video blog. This video blog develop using Multimedia Development Life Cycle (MDLC), where is contain 6 steps which is, concept, design, material collecting, assembly, testing and distribution. Final result of this video blog contains tips on how to make cinematic sequence, which are compiled using Adobe Premiere Pro CC 2017. Final video are implemented on the youtube website, after implemented the video, this video able to provide some tips to audience about content in this video blog.